THE IMPLEMENTATION OF MERDEKA CURRICULUM IN LEARNING ENGLISH AT MTSN 1 MAKASSAR - Putri, Nurkadri Raja; Ariyani, Amra; Fauzan, Muh. Miftah (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This research aims to find out the implementation of the Merdeka Curriculum in English language learning at school. The method used is descriptive qualitative with data collection techniques through observation and interviews. The research subjects consisted of two English teachers from MTsN 1 Makassar who were selected using purposive sampling. Based on the 3 stages of the research, the results show that, (1) Planning: Teachers prepare learning outcomes, flow of learning objectives, criteria for achieving objectives, learning modules, semester and annual programs, and analyze the Merdeka curriculum assessment system. Assessments encompass knowledge (oral tests and assignments), attitudes (observations), and skills (performance-based evaluations such as presentations and discussions). While both teachers showed good planning efforts, one demonstrated more thorough preparation than the other; (2) Implementation: Challenges include limited lesson hours for English. Despite this, students actively engaged in learning activities, such as quizzes and discussions, showing mastery of the material. Among the teachers observed, one (class VIII teacher) excelled in implementing the curriculum in alignment with the Pancasila profile; and (3) Evaluation: Teachers conduct formative and summative assessments effectively, fostering increased student activity and class participation. Merdeka Curriculum provides flexibility in teaching, allowing teachers to adapt materials according to student needs. Observations showed that teachers implemented an interactive learning approach, while interviews revealed the challenges and strategies faced in implementing the curriculum. This study concludes that despite the challenges, implementing the Merdeka Curriculum can increase student engagement in English language learning.